2007
DOI: 10.1016/j.adolescence.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational discrepancies of parental control among Chinese American families: Links to family conflict and adolescent depressive symptoms

Abstract: This study investigated how discrepancies between adolescents’ and parents’ endorsement of parental control contribute to adolescent depressive symptoms. Family conflict was hypothesized to mediate the link between parent–adolescent discrepancies and depressive symptoms. The sample consisted of 166 pairs of Chinese American adolescents and their parents. The results indicated that, as predicted, greater discrepancies between adolescents and their parents on parental control related to greater adolescent depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
111
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(124 citation statements)
references
References 28 publications
12
111
1
Order By: Relevance
“…The findings suggested a negative impact of low parental warmth and high intergenerational family conflict on depressive symptoms among Korean American adolescents. This result was consistent with previous reports (Cho and Bae, 2005;Juang et al, 2007;Kim and Cain, 2008;Park, 2003).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The findings suggested a negative impact of low parental warmth and high intergenerational family conflict on depressive symptoms among Korean American adolescents. This result was consistent with previous reports (Cho and Bae, 2005;Juang et al, 2007;Kim and Cain, 2008;Park, 2003).…”
Section: Discussionsupporting
confidence: 94%
“…The role of a mediator explains why and how such outcomes occur between independent and dependent variables. As a study reported, IFC partially mediated parental control on depressive symptoms among Chinese American adolescents (Juang et al, 2007); it is possible that IFC mediates between perceived parental warmth and depressive symptoms in the current study. In other words, if Korean American adolescents perceive less warmth from their parents, they may have a high level of IFC.…”
Section: Possible Mediating Role Of Intergenerational Family Conflictmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 6 studies combined host cultural gap higher with host cultural gap lower and/or native cultural gap higher with native cultural gap lower to test whether a gap in the host culture differs from a gap in the native culture [Elder, Broyles, Brennan, Zuniga de Nuncio, & Nader, 2005;Martinez, 2006;Phinney & Ong, 2002;Phinney & Veddar, 2006;Sam & Virta, 2003 Fa mily member respondent refers to the family member, in addition to the child/adolescent participant, who reported their acculturation level; number indicates the sample size of the study; cultural dimension refers to whether the measure takes a unidimensional or bidimensional approach and the culture of acculturation being measured (host culture vs. native culture); cultural domain refers to the particular aspects of acculturation that are being measured and whether the measure combines all domains into a global index of acculturation, independently examines multiple domains, or measures a single domain; calculation refers to how the acculturation gap was Expanding the Acculturation Gap-Distress Model 323 Human Development 2010;53:313-340 Chen, 1999]. Finally, 2 studies examined only 1 of the 4 types of gaps [Juang, Syed, & Takagi, 2007;Zhou, 2001]. …”
Section: Four Types Of Acculturation Gapsmentioning
confidence: 99%
“…Also, the author was not able to include several important factors, including perceived discrimination, family cohesion, and family conflicts in my analyses because of the lack of data on these measures from the non-Hispanic white sample. Previous studies have found the effects of these factors on mental well-being among Asian American populations to be significant yet nuanced, and the findings were less than consistent for the potential reasons regarding sampling frames and strategies Juang et al 2007). It should also be noted that over three quarters of the Chinese Americans in the study sample were first generation immigrants, which has skewed the findings among second and third-or-higher generation Chinese Americans.…”
Section: Discussionmentioning
confidence: 73%